Activation of somatostatin receptors attenuates pulmonary fibrosis. Issue 3 (19th October 2007) - Borie, R; Fabre, A; Prost, F; Marchal-Somme, J; Lebtahi, R; Marchand-Adam, S; Aubier, M; Soler, P; Crestani, B
Abstract : Background and aim: Somatostatin analogues may have antifibrotic properties in the lung. The aim of this study was to evaluate the expression of the five somatostatin receptors sst1 to sst5 in normal and fibrotic mouse lung and the action of SOM230 (pasireotide), a new somatostatin analogue with a long half-life, in bleomycin induced lung fibrosis and in human lung fibroblasts in vitro. Methods: After intratracheal injection of bleomycin, C57Bl6 male mice received one daily subcutaneous injection of SOM230 or saline. The lungs were evaluated on days 3, 7 and 14 after administration of bleomycin. Results: We found that all somatostatin receptors were expressed in the normal mouse lung. The sst2 receptor mRNA expression was increased after bleomycin. SOM230 improved mice survival (69% vs 44%; p = 0.024), reduced lung collagen content at day 14 and decreased lung collagen-1 mRNA at day 7. SOM230 reduced bronchoalveolar lavage inflammatory cell influx at day 3, decreased lung connective tissue growth factor mRNA and transforming growth factor (TGF) β mRNA and increased lung hepatocyte growth factor and keratinocyte growth factor mRNA. The sst2 receptor was strongly expressed in the human lung (normal or fibrotic), particularly by fibroblasts. In vitro, SOM230 reduced BrdU incorporation by control human lung fibroblasts cultured under basal conditions or with TGFβ, and reduced alpha-1 collagen-1 mRNA expression in TGFβ stimulated fibroblasts. Conclusion: We conclude that SOM230 attenuates bleomycin induced pulmonary fibrosis in mice and human lung fibroblasts activation. This study points to a potential new approach for treating pulmonary fibrotic disorders.